Experimental investigation of a novel sleeved member with additional friction dampers. (15th February 2023) - Gao, Jingwei; Wang, Chun-Lin; Zeng, Bin; Qiu, Tianyi
Highlights: Proposing a novel sleeved member with additional friction dampers (FSM). FSM exhibits similar lateral-constraint capacity to ordinary assembled sleeve member (ASM). Compared with ASM, FSM shows greater energy dissipation capacity under tiny displacement. Extrusion of core and sleeve has negligible effect on bolt clamping force of FSM damper. Abstract: A novel sleeved member with additional friction dampers, which is abbreviated as the frictional sleeved member (FSM) in this paper, was proposed to ensure the stability and greater energy dissipation of compression members in space structures. The FSM consisted of an inner core, an outer sleeve, and additional friction dampers. Two semicircular pipes were fastened by high-strength bolts to obtain the outer sleeve. Friction dampers using composite friction materials were distributed on both sides of the sleeve in the long-axis direction. Cyclic compression-unloading tests of four compression members were completed in this paper. The test results showed that the FSM exhibited the following characteristics compared with an ordinary assembled sleeve member (ASM): comparable lateral-constraint capacity, greater resistance, and greater energy dissipation capacity under tiny axial displacement (0–4 mm). Nonmetallic friction pads had a stable energy dissipation capacity and slight start-sliding displacement, which met the energy dissipation requirements of the FSM under tiny displacements. The additional friction dampers of the FSM had a slight effect on the deformation mode of the inner core, but the resistance and secant stiffness of the specimen were both significantly improved. The outer sleeve of the FSM adopted an asymmetric friction connection, leading to a periodic local increase and an overall decrease in the clamping force of the high-strength bolts. The extrusion between the outer sleeve and the buckling inner core had a negligible effect on the clamping force of the high-strength bolts.